Combining ability and heterosis analysis in linseed (Linum usitatissimum) for yield and oil quality - Kumar, Sanjiv; Kerkhi, S.A.; Singh, S.D.; Singh, Manender; Kumar, Anil (Annals of Agricultural Research, 2016)
An investigation on genetic analysis of yield and quality components in linseed (Linum usitatissimumL.) was undertaken to assess the genetic content of quality components of oil including fatty acid profile to pin point potential donors and cross combinations for their effective exploitation through appropriate breeding techniques for the improvement of desired traits in linseed. The study suggests that improvement in yield, oil content and linolenic acid can be achieved by fixing desirable genes by interse mating among the primary cross combinations such as Parwati × Shekhar, Parwati × T-397, Parwati × Himalini, Parwati × Padmini, Ayogi × Padmini, Shekhar × T-397, Shekhar × Padmini, Himalini × Padmini & Padmini × J-17 which are having high SCA effects for yield to break undesirable linkage and to get desirable genetic recombinants. The crosses Parwati × Himalini & Parwati × Shekhar were the best combinations for oil content.